Campylobacter Bacteriophage Cocktail Design Based on an Advanced Selection Scheme - Severin Michael Steffan; Golshan Shakeri; Corinna Kehrenberg; Elisa Peh; Manfred Rohde; Madeleine Plötz; Sophie Kittler (MDPI AG, 2022)
Campylobacteriosis is a worldwide-occurring disease and has been the most commonly reported zoonotic gastrointestinal infection in the European Union in recent years. The development of successful phage-based intervention strategies will require a better understanding of phage-bacteria interactions to facilitate advances in phage cocktail design. Therefore, this study aimed to investigate the effects of newly isolated group II and group III phages and their combinations on current Campylobacter field strains. A continuous workflow for host range and efficiency of plating (EOP) value determination was combined with a qPCR-based phage group identification and a liquid-based planktonic killing assay (PKA). An advanced analysis scheme allowed us to evaluate phage cocktails by their efficacy in inhibiting bacterial population growth and the resulting phage concentrations. The results of this study indicate that data obtained from PKAs are more accurate than host range data based on plaque formation (EOP). Planktonic killing assays with Campylobacter appear to be a useful tool for a straightforward cocktail design. Results show that a group II phage vB_CcM-LmqsCP218-2c2 and group III phage vB_CjM-LmqsCP1-1 mixture would be most promising for practical applications against Campylobacter coli and Campylobacter jejuni.